2013
DOI: 10.1002/jor.22313
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐fibrosis effect of BMP‐7 peptide functionalization on cobalt chromium alloy

Abstract: Orthopedic metallic prosthetic implants are commonly made of cobalt chromium (CoCr) alloys. However, such metal-based implants are susceptible to fibrous capsule formation on the implant surface after implantation. At the bone-implant interface, this capsule can prevent implant integration, resulting in loosening and failure. Minimizing the development of such a capsule on the CoCr surface would improve direct bone-implant bonding leading to long-term implant functionality. We evaluated the anti-fibrosis effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…Yang et al ( 28 ) demonstrated that BMP-7 inhibited silica-induced pulmonary fibrosis in rats by upregulating the expression of p-Smad1/5/8. In addition, p-Smad1/5/8 was demonstrated to be involved in BMP-7 signaling pathway-induced anti-fibrotic effects on fibrous capsule formation on the surface of orthopedic metallic prosthetic implants ( 29 ). Furthermore, increased expression of p-Smad1/5/8 was observed in mediating the anti-fibrosis effects of BMP-7 in the cornea ( 30 ) and lung ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al ( 28 ) demonstrated that BMP-7 inhibited silica-induced pulmonary fibrosis in rats by upregulating the expression of p-Smad1/5/8. In addition, p-Smad1/5/8 was demonstrated to be involved in BMP-7 signaling pathway-induced anti-fibrotic effects on fibrous capsule formation on the surface of orthopedic metallic prosthetic implants ( 29 ). Furthermore, increased expression of p-Smad1/5/8 was observed in mediating the anti-fibrosis effects of BMP-7 in the cornea ( 30 ) and lung ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve the bioactivity of CoCrMo have included chemical vapor deposition coating, 17 sol-gel coating, 18 ultraviolet photofunctionalization, 19,20 and immobilization with bone morphogenic peptides. [21][22][23] Surface modification of CoCrMo through topographical methods remains largely un-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they were washed with copious amounts water. Washed Ti substrates were coated with polydopamine (Ti-pDOP) as previously described [ 48 ]. In brief, Ti substrates were immersed overnight in dopamine solution (2 mg/mL of dopamine hydrochloride in 10 mM of Tris Buffer at pH = 8.5).…”
Section: Methodsmentioning
confidence: 99%